2005
DOI: 10.1016/j.jasms.2005.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Protonated adenine: Tautomers, solvated clusters, and dissociation mechanisms

Abstract: Ab initio and density functional theory calculations at the B3-MP2 and CCSD(T)/6-311 ϩ G(3df,2p) levels of theory are reported that address the protonation of adenine in the gas phase, water clusters, and bulk aqueous solution. The calculations point to N-1-protonated adenine (1 ؉ ) as the thermodynamically most stable cationic tautomer in the gas phase, water clusters, and bulk solution. This strongly indicates that electrospray ionization of adenine solutions produces tautomer 1 ؉ with a specificity calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 43 publications
12
94
1
Order By: Relevance
“…There is general agreement with earlier theoretical studies of the purine bases [36][37][38][39][40] and of cytosine [34,41]. The measured proton affinity of aniline is 874 kJ/mol (208.8 [42] and 209.5 kcal/mol [43] )and experimental [44] and theoretical [45] studies showed almost equal propensity for protonation at the amino-N-and the para-C-atoms.…”
Section: Site Of Protonation and Mode Of Initial Fragmentationsupporting
confidence: 88%
See 3 more Smart Citations
“…There is general agreement with earlier theoretical studies of the purine bases [36][37][38][39][40] and of cytosine [34,41]. The measured proton affinity of aniline is 874 kJ/mol (208.8 [42] and 209.5 kcal/mol [43] )and experimental [44] and theoretical [45] studies showed almost equal propensity for protonation at the amino-N-and the para-C-atoms.…”
Section: Site Of Protonation and Mode Of Initial Fragmentationsupporting
confidence: 88%
“…Data for guanine reported in reference [38]. Compare also [34,36] for proton affinities of cytosine and adenine, respectively. b Exp.…”
Section: Experimental and Computationalmentioning
confidence: 82%
See 2 more Smart Citations
“…1). However, the mechanistic details have not been explored (apart from an ab initio mechanistic study of the HCN dimerization and adenine protonation) (19,20). Experimental investigations would be very difficult because adenine is not formed cleanly, yields are small, and many steps are involved.…”
mentioning
confidence: 99%